The evolving work environment and employee engagement: organisational trust as a moderator - Lim, Wei Ling (2022)
The COVID-19 has brought about unprecedent changes within organisations, particularly with regards to the physical dimension of workplace. Overnight, work environment has evolved drastically from a physical conventional office to a virtual workplace, and now a fairly new concept of hybrid work model. Since the pandemic, employees in Malaysia have worked in all three types of work environments due to the implementation of Movement Control Order (MCO). Upon having to experience all three different work environments, literature has suggested conflicting opinions and experiences on both ends of the spectrum with regards to employees’ engagement at work. Given the above, the aim of this study is to research on the impact of different work environments on employee engagement. Further, the moderating role of organisational trust on the relationship between work environment and employee engagement will be explored. As organisations align themselves towards the COVID-19 endemic, the ultimate findings will suggest the preferred work environment of employers and employees in Malaysia. A mixed method approach has been adopted for this study. Quantitative data was collected through the medium of internet surveys distributed to all employees in Malaysia on a free sampling basis, to understand the impact of work environment on employee engagement from the perspective of employees. Meanwhile, qualitative data was acquired through online interview with Human Resource (HR) leaders, who represent the perspective of organisations, to explore the three variables, i.e., work environment, organisational trust, and employee engagement. Overall, the findings indicate that work environment is positively correlated to employee engagement. The impact of different work environments on employee engagement is distinct from one another. In addition, organisational trust is a crucial moderator for the relationship between work environment and employee engagement. Further recommendations have been provided, grounded by extensive literature review and findings collected. The practical implication of this study contributes to the betterment of human resource management practices. Additionally, this study contributes to the existing research and literature gap, owing to the fact that the evolvement of work environment is a recent phenomenon due to the COVID-19 crisis.